2021
DOI: 10.3390/ma14041031
|View full text |Cite
|
Sign up to set email alerts
|

Flash Sintering of YSZ/Al2O3 Composites: Effect of Processing and Testing Conditions

Abstract: The flash sintering behavior of yttria-stabilized zirconia/alumina composites was investigated to understand the role of the fundamental processing and testing parameters (electric field intensity, electric current limit, thermal insulation, homogeneity and dispersion of the two phases) on densification. A strong relation between the composite compositions and the electric parameters needed to promote flash sintering is revealed. Interestingly, the composite preparation method, which affects the two-phases dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…3 This "catalytic" effect of YSZ of `100 V cm -1 `100 V cm -1 `100 V cm -1 CHR:10 o C min - [2] [1] [3] present work F I G U R E 1 Arrhenius plots showing the flash onset for single phase 3YSZ, 8YSZ, and alumina, as well for 50/50 vol% particulate composites and bilayers. [1] and [2] are from Cologna et al, [3], for 50/50 particulate YSZ/alumina, from Naik et al, and the bilayer results are present work reported later in this article flash sintering of alumina has been further corroborated in recent papers [4][5][6] . The influence of the green microstructure has been rationalized in terms of the percolation of current through the composite.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…3 This "catalytic" effect of YSZ of `100 V cm -1 `100 V cm -1 `100 V cm -1 CHR:10 o C min - [2] [1] [3] present work F I G U R E 1 Arrhenius plots showing the flash onset for single phase 3YSZ, 8YSZ, and alumina, as well for 50/50 vol% particulate composites and bilayers. [1] and [2] are from Cologna et al, [3], for 50/50 particulate YSZ/alumina, from Naik et al, and the bilayer results are present work reported later in this article flash sintering of alumina has been further corroborated in recent papers [4][5][6] . The influence of the green microstructure has been rationalized in terms of the percolation of current through the composite.…”
Section: Introductionsupporting
confidence: 76%
“…Interestingly, the onset of flash depends not only on the volume fraction of YSZ but also on the homogeneity of the green microstructure 6 . A similar result was obtained in reactive flash sintering of alumina, magnesia, and 8YSZ to form a composite of magnesium aluminate spinel and YSZ, where agglomerated powders were easier to flash than more homogeneously milled powders 7 .…”
Section: Introductionsupporting
confidence: 62%
“…Despite its simplicity, FS is an extremely powerful sintering method that can be successfully used for most ceramic materials, from dielectrics (BaTiO 3 [41][42][43][44][45][46][47] or (Bi 0.2 Na 0.2 K 0.2 Ba 0.2 Ca 0.2 )TiO 3 [48]) to ionic (Zirconia, YSZ [2,[49][50][51][52], CeO 2 or doped-CeO 2 [53][54][55][56][57][58]) or electronic (TiO 2 [19,22,[59][60][61][62], BiFeO 3 or substituted-BiFeO 3 [24,27]) conductors. Interestingly, it can be also applied for processing ceramic composites of complex stoichiometry, metastable phases, or materials constituted by volatile species at the temperatures required for their sintering such as YSZ-Al 2 O 3 composites [63][64][65], different types of solid state electrolytes [25,66,67], BiFeO 3 [68,69], or K 0.5 Na 0.5 NbO 3 [26,[70][71][72][73]. Moreover, ceramics prepared by FS present very interesting properties rarely reported for materials obtained by convectional procedures.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest temperature of 850°C with a 120 V cm –1 DC electric field resulted in a fully densified sample within 5 seconds [8]. The flash sintering behaviour of the yttria-stabilised zirconia/alumina composites was investigated to understand the role of the fundamental processing and testing parameters (electric field intensity, electric current limit, thermal insulation, homogeneity and dispersion of the two phases) on densification [9]. Gadolinia-doped ceria, strontium titanate, MgO-doped alumina, undoped yttria and silicon carbide were also consolidated successfully by flash sintering at relatively lower temperatures than conventional sintering [10].…”
Section: Introductionmentioning
confidence: 99%